2021
DOI: 10.1182/blood-2021-145521
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Heterogeneity and Clonal Evolution in High Hyperdiploid Childhood Acute Lymphoblastic Leukemia

Abstract: High hyperdiploid (HeH) B-cell precursor acute lymphoblastic leukemia (BCP ALL) is characterized by a very specific nonrandom gain of chromosomes; a feature distinct from other types of aneuploid tumor types that usually display very heterogeneous gains and losses of chromosomes. Gains of chromosomes X, 4, 6, 10, 14, 17, and 18 are seen in more than 75% of cases of HeH childhood ALL, and of chromosome 21 in 100% of cases. In contrast to many aneuploid malignancies, there has been little evidence of chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A characteristic feature of the HeH subtype is the nonrandom gain of chromosomes, with an extra copy of chromosome 10, that carries ARID5B, being seen in 70% of cases. 5,17 We have previously reported that HeH ALLs that are constitutionally heterozygous for ARID5B risk alleles and with an acquired trisomy 10 more commonly gain the chromosome 10 homolog carrying the risk allele. 7 Here, we validate this finding in a much larger larger cohorts are needed to determine whether somatic ARID5B deletions are early or late events.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A characteristic feature of the HeH subtype is the nonrandom gain of chromosomes, with an extra copy of chromosome 10, that carries ARID5B, being seen in 70% of cases. 5,17 We have previously reported that HeH ALLs that are constitutionally heterozygous for ARID5B risk alleles and with an acquired trisomy 10 more commonly gain the chromosome 10 homolog carrying the risk allele. 7 Here, we validate this finding in a much larger larger cohorts are needed to determine whether somatic ARID5B deletions are early or late events.…”
Section: Discussionmentioning
confidence: 99%
“…Why this results in increased risk specifically for HeH ALL is not known. A characteristic feature of the HeH subtype is the nonrandom gain of chromosomes, with an extra copy of chromosome 10, that carries ARID5B , being seen in ~70% of cases 5,17 . We have previously reported that HeH ALLs that are constitutionally heterozygous for ARID5B risk alleles and with an acquired trisomy 10 more commonly gain the chromosome 10 homolog carrying the risk allele 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining chromosomes are also gained in subsets of cases, but at lower frequencies. 2,3 On the basis of the ubiquitous presence of extra chromosomes and findings showing that the chromosomal gains are present very early in leukemogenesis, [4][5][6][7][8] it is generally believed that the high hyperdiploidy is the main driver of leukemia development. How the extra chromosomes promote leukemogenesis remains, however, to a large extent unknown.…”
mentioning
confidence: 99%